Determinação da blindagem de um novo laboratório de pesquisa contendo um equipamento de Radiologia Intervencionista usando o método Monte Carlo - Silva, Aline Ferreira da (2020)
This work presents a study of the shielding for a laboratory, located at the Physics Institute of the Federal University of Uberlândia (UFU), that will contain an Interventional Radiology equipment which is no longer used for exams, and was donated by the Hospital das Clínicas/UFU. This new laboratory must be adapted to the new Resolução da Diretoria Colegiada No. 330 that replaced Portaria 453/98, Normative Instruction 53, which specifies and regulates the interventional radiology services, and document 147 of the National Council on Radiation Protection and Measures. To estimate the shielding offered by the laboratory, Monte Carlo simulations were used. The radiation exposure scenarios were modeled for different wall compositions containing bricks, cement, barite, air and an X-ray tube of an interventionist equipment. The public individuals were represented by voxelized male and female virtual anthropomorphic phantoms of MESH surface called MASH3 and FASH3, respectively. They were positioned in the vicinity of the laboratory in order to study and compare the conversion coefficients of the equivalent and effective doses received by them. The results were evaluated according to the conversion coefficients for the equivalent and effective doses, the transmission factor, the location and gender of the phantoms.